Ketuntasan Belajar Siswa Menggunakan Metode Giving Question Getting Answer Terhadap Kemampuan Koneksi Matematis Siswa - Denni Ismunandar; Farid Gunadi; Mochammad Taufan; Eryanti _ (Universitas Muhammadiyah Semarang, 2019)
Purpose this research is determine the effectiveness of using GQGA methods to students’ mathematics connection ability on vocational school. Methods in this research use quantitative methods. The sample selection by purposive sampling and the result is X class major in TKR. Result of this research is GQGA effective to students’ mathematics connection ability. This can be seen from the result of the students’ mathematics connection ability exceed KKM. Then using SPSS, significant of one sample t test smaller than alpha (0,05), and the result of the comparison of t observations with t table show that t observations greather than t table. Therefore, the GQGA method can be used in learning in Vocational Schools.